Decisão em colegiados e o papel dos conselhos diretores - o caso do Instituto Metodista Hendrix - Paradela, Clovis de Oliveira (1998)
The dissertation here presented demonstrates some of the aspects of the decision making process of the Board of Directors of the Methodist Institute Izabela Hendrix. This study is divided into na introduction and three chapters which show the means by which we carne to the conclusion presented at the end. In the introduction we have presented the principIe paradigm used in the decision making process by the Board of Directors of the Izabela, within the context of a history of the Methodist education. The first chapter presents a history of Methodist education which is in fact the history ofMetodism from its beginning in EngIand, the United States and in Brasil. The second chapter shows na approach to the principIe decision making process, whith emphasis on the decisions made in a group, as by members of the Board. The third chapter discusses the idea of a Boerd of Directors, presenting the historic development and otfering criticism of the present model in use as well as questioning the decision making process oflzabela. In chapter four, we propose a new madel for the Board os Directors of Izabela for this present moment in history. The role proposed in the conclusion is founded on the theoretic bases that guide the study of decision making process of Board of Directors, our educational mission and the organizationalm model of the Methodist Church, taking into consideration its beliefs and historical development.